Using movies as a tool in the teaching-learning process in medicine and health sciences PhD programs - Lavado Landeo, Lincoln (2020)
Objective: To evaluate the advantages of using movies as a tool in the teaching-learning process in medicine and health sciences PhD programs. Materials and methods: Twenty-one (21) PhD students participated in the study: nine (09) from the Universidad de San Martín de Porres (USMP) and twelve (12) from the Universidad Nacional Mayor de San Marcos (UNMSM). Thirteen (13) were males and eight (08) were females. Males’ average age was 43.54 and females’ was 56.75. The advantages of using movies in the courses of medicine and health sciences PhD programs were evaluated with a four-part questionnaire, out of which three (03) parts collected quantitative data (in scale from 1 to 10) and one (01) obtained qualitative data. Results: The average score of the answers of the first part (watching movies before classwork) was 9.60, the average score of the second part (classwork) was 9.67 and the average score of the third part (final result) was 9.48. Eight (08) PhD students voluntarily participated in the qualitative phase. Conclusions: Using movies proved to have great value in the teaching-learning process, because it not only enabled a better understanding of the courses’ topics but also played an important role in motivating the students. It is highly recommended to include audiovisual methods in the university teaching-learning process in medicine and health sciences PhD programs.